2014
DOI: 10.1016/j.celrep.2014.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Activation of DNA Damage Response Signaling by Condensed Chromatin

Abstract: Summary The DNA damage response (DDR) occurs in the context of chromatin structure, and architectural features of chromatin contribute to DNA damage signaling and repair. While the role of chromatin decondensation in the DDR is established, we show here that chromatin condensation is integral to DDR signaling. We find that upon DNA damage, chromatin regions transiently expand before undergoing extensive compaction. Using a protein-chromatin tethering system to create defined chromatin domains, we show that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
158
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(188 citation statements)
references
References 87 publications
(129 reference statements)
21
158
1
1
Order By: Relevance
“…Previous studies have shown a global chromatin relaxation followed by either restoration or further compaction upon UV irradiation (Burgess et al, 2014;Rubbi and Milner, 2003;Soria et al, 2012). Our findings show a genome-wide loss of chromatin accessibility at 6 h after UV exposure, irrespective of the genomic location, which consolidates our previous observation indicating a potential cellular mechanism to protect genome and transcriptome integrity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies have shown a global chromatin relaxation followed by either restoration or further compaction upon UV irradiation (Burgess et al, 2014;Rubbi and Milner, 2003;Soria et al, 2012). Our findings show a genome-wide loss of chromatin accessibility at 6 h after UV exposure, irrespective of the genomic location, which consolidates our previous observation indicating a potential cellular mechanism to protect genome and transcriptome integrity.…”
Section: Discussionsupporting
confidence: 78%
“…In this direction, a recent study has shown that, upon UV irradiation, chromatin transiently undergoes de-condensation to allow binding of several repressive factors such as the polycomb complex component BMI1, the nucleosome-remodeling deacetylase complex (NuRD) as well as the heterochromatin protein HP1 and the HP1-binding protein 3 (HP1BP3) (Izhar et al, 2015). Another study proposes that during the response to UV irradiation, recruitment of repressive complexes induces condensation of chromatin to protect DNA from further potential damage (Burgess et al, 2014). Until now, the function and the resultant chromatin changes following recruitment of these complexes remains controversial (Papamichos-Chronakis and Peterson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Current techniques to study these processes require cell fixation, such as immunofluorescent identification of the rapidly phosphorylated histone H2A.X (Îł-H2A.X) subunit (30) or transfection using photoactivatable proteins (33,34). Furthermore, fluorescent visualization of cell viability for drug screening often requires the use of cell-permeant minor-groove binding dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Burgess et al have shown that chromatin condensation per se can trigger an initial DNA damage response, which results in the recruitment of several DDR factors including MDC1. 89 Accordingly, MDC1 forms spontaneous foci on the condensed mitotic chromosomes. 57,89 MDC1 is required for TopBP1 recruitment to stalled forks in response to replication stress.…”
Section: Processing Of Underreplicated Regions and Joint Molecules Inmentioning
confidence: 99%
“…89 Accordingly, MDC1 forms spontaneous foci on the condensed mitotic chromosomes. 57,89 MDC1 is required for TopBP1 recruitment to stalled forks in response to replication stress. Similar to this mechanism, MDC1 accumulation due to condensation could explain the high number of spontaneous TopBP1 foci on mitotic chromatin.…”
Section: Processing Of Underreplicated Regions and Joint Molecules Inmentioning
confidence: 99%